2009
DOI: 10.1021/ja8091104
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Dependent Targeting of Cancer Cells by Bleomycin−Microbubble Conjugates

Abstract: Biotinylated bleomycin A(5) was attached to streptavidin-derivatized microbubbles, and a solution containing the conjugate was passed over a monolayer of cultured MCF-7 cells. The bleomycin-derivatized microbubbles adhered to the MCF-7 cells, and the association could be monitored by the use of a microscope. Three other cancer cell lines gave similar results. The bleomycin-microbubble conjugate did not bind to a normal breast cell line (MCF-10A) or to the matched noncancer cell lines corresponding to the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 24 publications
1
60
0
Order By: Relevance
“…5 Microbubbles, used traditionally as contrast agents for ultrasonography, have recently been modified with ligands that bind to specific receptors on cancer (and other) cell surfaces in an effort to probe ligand-cell surface interactions. 6 For this study, the C-terminus of BLM was acylated with biotin and bound to commercially available streptavidin-derivatized microbubbles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Microbubbles, used traditionally as contrast agents for ultrasonography, have recently been modified with ligands that bind to specific receptors on cancer (and other) cell surfaces in an effort to probe ligand-cell surface interactions. 6 For this study, the C-terminus of BLM was acylated with biotin and bound to commercially available streptavidin-derivatized microbubbles.…”
mentioning
confidence: 99%
“…It was shown that BLM-derivatized, but not streptavidin-derivatized microbubbles bound to MCF-7 human breast carcinoma cells but not to the “normal” MCF-10A breast cell line. 5 To define the structural elements in BLM responsible for tumor targeting, the same experiment was performed using deglycoBLM, i.e. lacking the disaccharide moiety.…”
mentioning
confidence: 99%
“…3 It is employed for the treatment of several types of cancer, notably squamous cell carcinomas and malignant lymphomas. 4 The therapeutically useful effects of bleomycin are believed to be due both to its unique ability to target tumor cells selectively 5,6 and its ability to mediate double-strand cleavage of DNA. 7 …”
mentioning
confidence: 99%
“…15,21,22 The dye Cy5** was chosen as the fluorescent probe to circumvent initially encountered problems of autofluorescence and nonspecific cell surface binding. Cys5** is a cyanine dye exhibiting emission wavelengths in the red or near-infrared region.…”
Section: Discussionmentioning
confidence: 99%